EPIDEMI KORUPSI DALAM PALAGAN KEPENTINGAN IDEOLOGIS: Quo vadis Indonesia? - Valentinus Saeng (Litbang STFT Widya Sasana Malang, 2015)
Most people think until now that the problem of corruption is rooted in subject’s incapacity to internalize ethical and moral teachings. Analyzing critically relations and interactions between nations that is loaded with universe of interest, public understanding of corruption must be changed. The issue of corruption goes beyond the ethical-moral and psychological sphere. The corruption today has been transformed into an instrument of domination and of ideological struggle. It belongs integrally to neo-colonialism and neo-imperialism strategy of domination and exploitation.